Limites e desafios para objetivação da pedagogia histórico-crítica na prática escolar - Magalhães, Carlos Henrique Ferreira (2009)
The present research aimed at identifying the challenges faced by the municipal teachers of Sarandi (Paraná State) on the objectivization of the Historical-Critical Pedagogy for the Municipal General Office of Education from 2001 to 2008. To guide the research we had as general objective: to analyze the limits and challenges of objectivization of the school practice in the current routine based on the Historical-Critical Pedagogy. Based on documents, on meetings observations in the Municipal General Office of Education and in the investigated school, after participation on the VII Education Meeting and the interviews accomplished with the teachers in the school as well as with the Municipal Secretary of Education and their assistants, with the study of a national, state, and municipal history of the economy-politics, we understood that the founding aspect of the social being, his/her work built historically in the past acts in the present time as a ghost. The economical and extra-economical aspects continually and contradictorily take action in the formation of a social human being. The precarious conditions of the teachers initial and continuous formation, the organization of the school practice with neo- new school characteristics in previous administrations, the absence of factual conditions in the present time for the development of an emancipative school practice, the idealistic thinking regarding the State, the alienated work and the capital, among other facts, correspond to the multiple determinations that challenge the objectivization of an emancipative school practice or the Historical-Critical Pedagogy, in the current history, as a fight of classes. We concluded that the impediments for the objectivization of the Historical-Critical Pedagogy are in the objective conditions of the quotidian, promoted by the current capitalist sociability, as well as in the subjective conditions of estrangement of the faculty and members of the Municipal General Office of Education in relation to themselves, in relation to others and in relation to the reality. We understood that it urges to the faculty the need to seek their development as a human being, along with other extra-parliamentary movements in the organization of a radical politics. Thus, eventually, we may think about aiming at an emancipative school practice to struggle against the current prehistory on behalf of a history of men freely associated.